Textography as a needs analysis and research tool for English for Academic Purposes and learning development practitioners - Sizer, Jennifer (Journal of Learning Development in Higher Education, 2019)
The purpose of this paper to introduce textography as a useful method for English for academic purposes (EAP) and learning development (LD) practitioners to fill gaps in subject-specific knowledge and understanding. Textography is a research method that may be new to many practitioners. Textography combines textual analysis, usually associated with EAP, and ethnographic methods, often associated with LD, to investigate contexts, texts and practices. EAP and LD practitioners can use textography with accessible texts as initial needs analysis before reviewing literature or as a more in-depth, long-term research tool.